Greed and Irresponsibility, other causes from crisis? - Gonzales, Pedro (2011)
The failure of the economic formulas, post crisis financials, applied in several countries in the world aiming for the recovery of the global economy, the over- flow of greed and irresponsibility that continues giving to the money market an excessive indebtedness coming from the most developed countries, the existence of an exorbitant financial economy facing to the real economy, constant instability on the economic and financial world system facing to the financial ruin of some countries that offer us opportunities to explore new approaches for facing econo- mic and financial crisis. This text takes from a non conventional way, the existence of other causes that promote this kind of economic crisis, are arisen ideas based in supportive economy principles which has biblical precedents and that refers a greater commitment and social responsibility coming from the individuals, corpo- rations and countries.